Decreased Hemolysis and Improved Platelet Function in Blood Components Washed With Plasma-Lyte A Compared to 0.9% Sodium Chloride. Issue 2 (6th June 2018) - Refaai, Majed A; Conley, Grace W; Henrichs, Kelly F; McRae, Hannah; Schmidt, Amy E; Phipps, Richard P; Spinelli, Sherry L; Masel, Debra; Cholette, Jill M; Pietropaoli, Anthony; Eaton, Michael P; Blumberg, Neil
Abstract: Objectives: Washing cellular blood products is accepted to ameliorate repeated severe allergic reactions but is associated with RBC hemolysis and suboptimal platelet function. We compared in vitro hemolysis and platelet function in blood components after washing with Plasma-Lyte A (PL-A) vs normal saline (NS). Methods: RBC (n = 14) were washed/resuspended in NS or PL-A. Free hemoglobin and heme were determined at 0, 24, 48, and 72 hours. Platelet concentrates (PCs; n = 21) were washed with NS or PL-A and resuspended in same washing solution (n = 13) or ABO-identical plasma (n = 8). Platelet aggregation and spreading were evaluated. Results: The 24-hour free hemoglobin and heme levels were higher in NS ( P < .05). Improved platelet function was observed in PL-A-washed PCs ( P < .001). Discussion: PL-A showed less RBC hemolysis and better platelet function than NS. Whether such differences would occur in vivo is unknown.